DEVELOPMENT OF INTERACTIVE LEARNING MULTIMEDIA ON THE TOPIC ALHAMDULILLAH I CAN PRAY FOR ELEMENTARY SCHOOLS - Pipit Rika Wijaya; Fajar Isman (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
Integrating educational instruments into classroom dynamics is a crucial element for stimulating enthusiasm while sharpening students' cognitive competencies. In Islamic Education, specifically within the competency unit "Alhamdulillah, Aku Bisa Salat," indications of low motivation and learning outcomes that have not yet met expectations were found. To address these issues, an innovation in the form of interactive multimedia development based on the Lumi Education platform was introduced as a strategic solution to facilitate the assimilation of material. This research adopts the 4D development model (Define, Design, Develop, Disseminate) to produce a product that is both valid and applicable. The study involved a sample of 13 second-grade students at SDN 2 Landangan. Based on validation tests, media experts gave high praise with a score of 96%, while material experts provided a rating of 89%, both of which fall into the "Highly Feasible" category. Positive responses also came from the students, with a satisfaction percentage reaching 86%. This confirms that the use of Lumi Education is not only effective in helping students master the theory of worship at school but also provides practical readiness for implementing prayer procedures in community life, while improving student learning outcomes and motivation in a practical manner.